1983
DOI: 10.1083/jcb.97.6.1875
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus laevis lectin is localized at several sites in Xenopus oocytes, eggs, and embryos.

Abstract: The endogenous lectin of Xenopus laevis oocytes, unfertilized eggs, and blastulastage embryos was immunohistochemically localized using a highly specific antiserum . Each tissue was examined with several techniques, including paraformaldehyde or glutaraldehyde fixation, frozen or plastic sections, and immunofluorescence or immunoperoxidase staining. In oocytes and unfertilized eggs, lectin was detected in association with yolk platelets, cortical granules, and the vitelline envelope . In embryos, cortical gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…However, hIntL was also expressed on various tissues other than oocytes, and it has been reported that the other homologues are also present in various tissues (26,28,40). Thus, hIntL and its homologues may not only participate in formation of the fertilization envelope but also have other physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, hIntL was also expressed on various tissues other than oocytes, and it has been reported that the other homologues are also present in various tissues (26,28,40). Thus, hIntL and its homologues may not only participate in formation of the fertilization envelope but also have other physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…The rat lectin showed one major protein band with M, -14 .500 when examined by PAGE (Fig. 2), but there was also a clear minor band with M, 29,000 and a small amount of protein trailing behind the major band. On the basis of microdensitometry (Fig.…”
Section: Lectin Purificationmentioning
confidence: 99%
“…On the contrary, Roberson and Barondes (15) did not detect the lectin in VC of either unfertilized or fertilized eggs. The possibility that they used an antiserum other than that used by Greve and Hedrick (6) or in the present work must be excluded by comparison of the biochemical natures of the antigens (12,14,23,24).…”
Section: Discussionmentioning
confidence: 98%
“…From immunocytochemical observations on specimens embedded in a plastic resin, Greve and Hedrick (6) concluded that CGLs were present in the F layer and the perivitelline space, but not in the VC. However, Roberson and Barondes (15) could not confirm the presence of lectin in the fertilization coat (which probably consists of the VC plus the F layer), but they detected lectin in the cortical granules in sections embedded in plastic. These discrepant results were probably due to differences in immunohistochemical techniques and/or limited resolution by light microscopy.…”
Section: Introductionmentioning
confidence: 99%